Consumo de subsistencia de agua potable Avances de investigación sobre el consumo básico - Caro, José Lizcano; Rey Gutiérrez, Eladio; Rozo, Carlos Yezid (Tecnogestión: Una mirada al ambiente, 2015)
The planning of public services and their projection medium and long term is mandated by Act 142 of 1994 The growth of the population and their settlement in homogeneous geo zones, which determine the average amount of drinking water, and the evolution of endowments, helps to determine the variable horizon of the present value of the claim. Establish a methodology to approximate subsistence consumption is the purpose of the investigation, "Methodology and socio-economic model to estimate subsistence consumption of drinking water in Colombia. Academic and industry "Hits. In this paper, presents an introduction to scientific work, exposing some of the elements, equations and information considered for development. In particular, the result is shown to evaluate the vital minimum of water, calculated between the lower and upper limits of the possible courses of baseline.